Leading a Diversity Culture Shift: The Chair's Integral Role - Edna Chun (Academic Chairpersons Conference Proceedings, 2018)
Academic leaders are often challenged when faced with dealing with diversity cultural change. since change can be viewed as political, difficult, and unappealing. The influential role of department chairs as diversity cultural change agents working at the heart of the academic enterprise has often been overlooked. This highly interactive seminar offers a practical guide to leading culture change for diversity in the academic department based on interviews with diversity officers and institutional leaders. From a systems perspective, the seminar examines the integral role of organizational learning in the cultural change process. Through specific case study examples, exercises, and breakout discussions, the seminar will assist department chairs by sharing concrete strategies for initiating and implementing diversity culture change.
Keywords: Leading Diversity Culture Shift Integral Chair